Berry quality of hybrid grapevine (Vitis) cultivars grown in the field and in a polytunnel - Mariana Maante-Kuljus; Ele Vool; Leila Mainla; Marge Starast; Kadri Karp (Agricultural and Food Science, 2019)
The aim of this research was to determine the effect of vineyard location and cultivation system (polytunnel compared to field) on hybrid grapevine berry quality in cold climate conditions. The study was conducted with the hybrid grapevine cultivars ‘Hasanski Sladki’, ‘Zilga’ and ‘Supaga’. Experimental vineyards were located at different sites in a polytunnel and in the field. Soluble solids content ranged from 13.8 to 25.4 °Brix. For all cultivars cultivation in the tunnel had a positive effect on soluble solids content for two experimental years out of three. Acid content was high, ranging from 1.04 to 1.76 g 100 g-1 FW. Growing ‘Zilga’ and ‘Supaga’ in the tunnel reduced titratable acid content every year but for ‘Hasanski Sladki’ in two years. Phenolic content ranged from 53 to 540 g 100 g-1 FW and anthocyanin from 30 to 162 mg 100 g-1 FW. Accumulation of phenols and anthocyanins were affected by location and cultivation methods. For ‘Hasanski Sladki’ in the tunnel, cultivation had a positive effect on phenolic content but for ‘Zilga’ not in every year.